Smart Method To Determine Home Ownership Credit Financing Liquidity Facility For Housing Financing (KPR FLPP) For Low-Income Communities In Medan City (Case Study : Bank Syariah Indonesia) - Dedi Leman (JAIA - Journal of Artificial Intelligence and Applications, 2021)
Population growth in Indonesia is always increasing every year so that the number of residential needs also increases. Higher house installaments make people think twice before buying a house. The lack of information about subsidied housing makes people think that the prices of some houses are relatively expensive so people choose to contract which will certainly drain income. Subsidied housing is an untaxed plus house with low interest. On the research this time using a Decision Support System that is called the option-based housing support system, using the smart method, which is able to help people select subsidied housing to fit the need. The implementation of this method aims to facilitate the selection of subsidied housing based on calculations from the criteria used as locations, public facilities, access to locations, the quality of buildings and the credibility of developers. The results of this system provide solutions in the form of the best alternatives to be determined based upon the ranking of smart calculations.